Improved Whole Gamma Irradiated Avian Influenza Subtype H9N2 Virus Vaccine Using Trehalose and Optimization of Vaccination Regime on Broiler Chicken - Motamedi Sedeh, Farahnaz; Khalili, Iraj; Wijewardana, Viskam; Unger, Hermann; Shawrang, Parvin; Behgar, Mehdi; Moosavi, Sayed Morteza; Arbabi, Arash; Hosseini, Sayedeh Maede (Frontiers in Veterinary Science, 2022)
Gamma (γ)-radiation can target viral genome replication and preserve viral structural proteins compared to formalin inactivation. Thus, a stronger immunity could be induced after inoculation of the irradiated virus. In this study, γ-irradiated low pathogenic avian influenza virus-H9N2 (LPAIV-H9N2) was used to immunize the broiler chicken in two formulations, including γ-irradiated LPAIV-H9N2 with 20% Trehalose intranasally (IVT.IN) or γ-irradiated LPAIV-H9N2 plus Montanide oil adjuvant ISA70 subcutaneously (IV+ISA.SC) in comparison with formalin-inactivated LPAIV-H9N2 vaccine intranasally (FV.IN) or formalin-inactivated LPAIV-H9N2 plus ISA70 subcutaneously (FV+ISA.SC). Two vaccination regimes were employed; the first one was primed at day one and boosted at day 15 (early regime), and the second one was primed at day 11 and boosted at day 25 (late regime). A challenge test was performed with a live homologous subtype virus. Virus shedding was monitored by quantifying the viral load via RT-qPCR on tracheal and cloacal swabs. Hemagglutination inhibition (HI) antibody titration and stimulation index (SI) of the splenic lymphocyte proliferation were measured respectively by HI test and Cell Proliferation assay. Cytokine assay was conducted by the RT-qPCR on antigen-stimulated spleen cells. The results of the HI test showed significant increases in antibody titer in all vaccinated groups, but it was more evident in the IVT late vaccination regime, reaching 5.33 log2. The proliferation of stimulated spleen lymphocytes was upregulated more in the IVT.IN vaccine compared to other vaccines. The mRNA transcription levels of T-helper type 1 cytokines such as interferon-gamma (IFN-) and interleukin 2 (IL-2) were upregulated in all vaccinated groups at the late regime. Moreover, IL-6, a pro-inflammatory cytokine was upregulated as well. However, upregulation was more noticeable in the early vaccination than the late vaccination (P<0.05). After the challenge, the monitoring of virus shedding for the H9 gene represented an extremely low viral load. The body weight loss was not significant (P>0.05) among the vaccinated groups. In addition, the viral load of less than 100.5 TCID50/mL in the vaccinated chicken indicated the protective response for all the vaccines. Accordingly, the IVT vaccine is a good candidate for the immunization of broiler chicken via the intranasal route at late regime.